Análise espacial das condições ecoepidemiológicas para estabelecimento da Esquistossomose mansonica em duas áreas do Distrito de Mosqueiro, Belém-PA - PEREIRA, Alba Lúcia Ribeiro Raithy (Universidade Federal do Pará, 2017)
The dynamics process of Mansonic Schitomiasis endemization is multifactorial, which sometimes retards it’s installation process, but also difficult the control of epidemiological surveillance. The Geo-technologies have brought contributions to the public health, creating thematic maps that make easier understand of dynamic population at space used, and their interrelationship with the water resources and with the sickness process. The proposal of this work was to identify through spatial analysis the eco-epidemiological factors related with the Mansonic Schitosomiasis endemization. It was achieved a descriptive study in two coverage areas from Family Health Strategy, Carananduba and Furo das Marinhas, In Mosqueiro District, Belém-PA, between 2010 and 2012, using geoprocessing Techniques like: Remote Sensing and Geographic Information Systems (GIS), through the tools: ERDAS 8.3.1 and ENVI 4.5, for classification of these satellites images, with the variables: Soil, vegetation cover and hydrography; The Global Positioning System (GPS) for georreferencing at study area and capturing collecting points of breeding sites; and ARCGIS 9.3.1 for manipulation and teatring of the Geographic Data Banks and Kernel estimation for identification of risk zones about high resolution satellite images and cartographic bases. Were analyzed, also, environmental and ecological data through geoprocessing techniques. The geo-technologic tools producing thematic maps of Family Health Strategic abrangency, the work routes, environmental classification, and the localization of breeding sites that generating seven agglomerated Kernel points that identified the risk zones of transmission aggravating in 3 boroughs of Carananduba Zone. This zone has been presenting antrophic characteristics due disordered human occupation and hydro siltation collections. The Furo das Marinhas area still keeps native forest and great quantity of hydro collections yet and not being found Biomphilaria. In both studied areas the structure of sanitation is insufficient, and isn’t still there focus active of transmission from Mansonic Schitosomiasis. However, could be a great vulnerability in a short time to happen this incidence at Caranaduba area. So, the geo-technologies applied have enabling a geographic information system that made feasible the diagnostic of risk on the process of Mansonic Schitosomiasis Endemization in more than one location in Para.